Mouse sperm K(+) currents stimulated by pH and cAMP possibly coded by Slo3 channels - Martínez-López, Pablo (2009)
Slo3 channels belong to the high conductance Slo K(+) channel family. They are activated by voltage and intracellular alkalinization, and have a K(+)/Na(+) permeability ratio (P(K)/P(Na)) of only approximately 5. Slo3 channels have only been found in mammalian sperm. Here we show that Slo3 channels expressed in Xenopus oocytes are also stimulated by elevated cAMP levels through PKA dependent phosphorylation. Capacitation, a maturational process required by mammalian sperm to enable them to fertilize eggs, involves intracellular alkalinization and an increase in cAMP. Our mouse sperm patch clamp recordings have revealed a K(+) current that is time and voltage dependent, is activated by intracellular alkalinization, has a P(K)/P(Na)≥ 5, is weakly blocked by TEA and is very sensitive to Ba(2+). This current is also stimulated by cAMP. All of these properties match those displayed by heterologously expressed Slo3 channels, suggesting that the native current we observe in sperm is indeed carried by Slo3 channels.